A decentralized-based blockchain framework for scientific manuscript peer-review - Cajas Guncay, Julio Rogers (2023)
The peer-review is the traditional process that a scientific journal implements prior to the publication of a research. The purpose of this procedure is for other experts to carry out a rigorous and consistent review of the submitted manuscript, and in this way they verify the veracity of the results. However, this review technique has received various criticisms throughout its existence. Including concerns about the low quality of the reviews, the high cost of publication, the lack of transparency of the review, the non-remuneration of reviewers, among others. Several alternatives proposals have been raised to provide a solution or improvement to these challenges. However, these solutions have not been transcendental. In recent years, proposals using blockchain technology and the benefits that a decentralized system offers have appeared. The problem with these proposals is that they tend to be theoretical, simple, or limited. This graduation project is presented as a better blockchain alternative that encompasses more qualities around the peer-review. This work propose a decentralized system that houses scientific journals that wish to use a peer-review infrastructure with different types of protocols. These protocols take advantage of the benefits of blockchain technology to solve or improve the challenges of the existing peer-review. Through the use of smart contracts, the interoperability of the proposal is evaluated. As well as the execution and transaction time, the computational costs and the real cost in ethers and dollars. These metrics are compared with the ones obtained by other proposals based on blockchain. The results show that the costs of this proposal tend to be higher due to the fact that it incorporates more functionalities, which allows a better operability and quality of the process of each magazine.